EU financial integration: Is there a 'Core Europe'? Evidence from a cluster-based approach - Thomas Kiehlborn; Mark Mietzner (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2005)
Numerous recent studies, e.g. EU Commission (2004a), Baele et al. (2004), Adam et al. (2002), and the research pooled in ECB-CFS (2005), Gaspar, Hartmann, and Sleijpen (2003), have documented progress in EU financial integration from a micro-level view. This paper contributes to this research by identifying groups of financially integrated countries from a holistic, macro-level view. It calculates cross-sectional dispersions, and innovates by applying an inter-temporal cluster analysis to eight euro area countries for the period 1995-2002. The indicators employed represent the money, government bond and credit markets. Our results show that euro countries were divided into two stable groups of financially more closely integrated countries in the pre-EMU period. Back then, geographic proximity and country size might have played a role. This situation has changed remarkably with the euro's introduction. EMU has led to a shake-up both in the number and composition of groups. The evidence puts a question mark behin d using Germany as a benchmark in the post-EMU period. The findings suggest as well that financial integration takes place in waves. Stable periods and periods of intense transition alternate. Based on the notion of 'maximum similarity', the results suggest that there exist 'maximum similarity barriers'. It takes extraordinary events, such as EMU, to push the degree of financial integration beyond these barriers. The research encourages policymakers to move forward courageously in the post-FSAP era, and provides comfort that the substantial differences between the current and potentially new euro states can be overcome. The analysis could be extended to the new EU member countries, to the global level, and to additional indicators.
urn:nbn:de:hebis:30-17611
Keywords: F3; F36; G15; 330; Financial integration process; country groups; core Europe; cluster analysis